KNOWLEDGE BASED RECOMMENDATION MODELING FOR CLOTHING PRODUCT SELECTION RECOMMENDATION SYSTEM - Vihi Atina; Dwi Hartanti (Informatika, Universitas Jenderal Soedirman, 2022)
One of the markets which is the largest wholesaler of clothing in Central Java is the Klewer market area and its surroundings. The Simple Inc Store is one of the clothing stores in the area. Simple Inc Store is a large kiosk that sells clothing products in the form of various types of t-shirts, shirts, jackets, sweaters and pants. Sales of products in these stores are still done conventionally, namely customers come directly to the store to choose and buy products. The number of clothing products that are sold makes customers experience difficulties in the process of selecting clothing products. Therefore, it is necessary to develop a recommendation system that can assist customers in choosing clothing products. The purpose of this research is to create a Knowledge Based Recommendation model for the Recommendation System for Selection of Clothing Products. The system development method used in this research is Rapid Application Development (RAD), which consists of stages, namely business modeling, data modeling and process modeling. The recommendation system method used in this research is knowledge based recommendation. Knowledge based recommendation has the advantage of being able to set the level of user priority based on the user's needs for the product by calculating the similarity value between customer needs and clothing product attributes. Knowledge based recommendation modeling for this clothing product selection recommendation system can provide 5 choices of clothing product search attributes, namely brand, price, material, color and size. Based on the results of modeling the knowledge based recommendation method with 20 sample data, it can provide recommendations for clothing products based on the criteria needed by customers by calculating the similarity value between customer needs and the attributes possessed by each clothing product. Clothing products with the highest similarity value will be displayed as a result of clothing product recommendations, namely the highest similarity value of 0.6 is obtained for Maternal t-shirts. The results of this knowledge-based recommendation modeling can be used as a reference in developing a recommendation system for the selection of clothing products.